Advanced Technologies for Large Scale Supply of Marine Drugs - Henar Martínez; Mercedes Santos; Lucía Pedraza; Ana M. Testera (Marine Drugs)
Marine organisms represent a source of unique chemical entities with valuable biomedical potentialities, broad diversity, and complexity. It is essential to ensure a reliable and sustainable supply of marine natural products (MNPs) for their translation into commercial drugs and other valuable products. From a structural point of view and with few exceptions, MNPs of pharmaceutical importance derive from the so-called secondary metabolism of marine organisms. When production strategies rely on marine macroorganisms, harvesting or culturing coupled with extraction procedures frequently remain the only alternative to producing these compounds on an industrial scale. Their supply can often be implemented with laboratory scale cultures for bacterial, fungal, or microalgal sources. However, a diverse approach, combining traditional methods with modern synthetic biology and biosynthesis strategies, must be considered for invertebrate MNPs, as they are usually naturally accumulated in only very small quantities. This review offers a comprehensive examination of various production strategies for MNPs, addressing the challenges related to supply, synthesis, and scalability. It also underscores recent biotechnological advancements that are likely to transform the current industrial-scale manufacturing methods for pharmaceuticals derived from marine sources.